In vitro evaluation of photon and carbon ion radiotherapy in combination with cisplatin in head and neck squamous cell carcinoma cell lines - Fang, Xumeng; Sun, Pian; Dong, Yuanli; Huang, Yangle; Lu, Jiade Jay; Kong, Lin (Frontiers in Oncology, 2023)
Background: Heavy ion radiotherapy, such as carbon ion radiotherapy (CIRT), has multiple advantages over conventional photon therapy. Cisplatin, as a classic anti-tumor drugs, has been tested and discovered as a photon radiosensitizer in several cell lines, including head and neck squamous cell carcinoma (HNSCC). Hence, the aim of our study is to evaluate whether cisplatin can sensitize CIRT towards HNSCC cell lines in vitro. Methods: Human nasopharyngeal carcinoma cell line CNE-2, human tongue squamous carcinoma cell line TCA 8113 and human hypopharynx squamous carcinoma cell line FADU were all irradiated with photon beam of 2, 4, 6, 8 Gy (physical dose) and carbon ion beam of 1, 2, 3, 4 Gy (physical dose) and treated with cisplatin. Cell survival was assessed by clonogenic survival assay. Results: CIRT showed significantly stronger cytotoxic effect than standard photon radiotherapy. The relative biological effectiveness (RBE) of carbon ion beam at 10% survival (〖RBE〗_10) was calculated 3.07 for CNE-2, 2.33 for TCA 8113 and 2.36 for FADU. Chemoradiotherapy (both photon radiotherapy and CIRT) was more effective than radiotherapy alone. In vitro sensitizer enhancement ratios (SERs) of cisplatin in CNE-2, TCA 8113 and FADU cell lines after photon irradiation were 1.33, 1.14 and 1.21, while after carbon ion irradiation were 1.02, 1.00 and 0.96, showed that cisplatin sensitized photon irradiation but showed no sensitization effect in carbon ion irradiation in all tested cell lines. Conclusions: In conclusion, high LET CIRT was more effective than photon irradiation to prevent the proliferation of HNSCC cell lines. Additional treatment with cisplatin could sensitize photon irradiation but showed no effect on carbon ion irradiation.